Kidfluencing: The Role of Calls to Action, Logo Presence, and Disclosure Modality on Parental Appraisals. Issue 3 (3rd July 2022) - Freeman, Jason; Dardis, Frank
Abstract: Kidfluencers are emerging as valuable brand partners capable of facilitating peer-to-peer interactions with other child viewers. The current experimental study focuses on the role of disclosure modality, call to action (CTA), and logo presence on parental reactions to kidfluencer content. Findings suggest that the negative consequences of advertising recognition can be ameliorated through sponsorship transparency. However, for some parents, advertising recognition led to greater perceived negative effects of advertising, resulting in unfavorable brand outcomes. These results suggest that advertising recognition can have diverging consequences. Advertising recognition was a primary predictor for a desire to regulate, attitudes toward the brand, and purchase intention. Practical and theoretical implications are discussed.